Median Palatine Cyst - Queiroz, Thallita Pereira; Scartezini, Guilherme Romano; Gomes de Souza Carvalho, Abrahao Cavalcante [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; dos Santos, Pamela Leticia [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Lippincott Williams & Wilkins, 2011)
The median palatine cyst is a rare benign nonodontogenic lesion that attacks the median palatine suture. There is controversy about its pathogenesis; however, its origin is generally attributed to the enclavement of epithelial remnants within the palatine suture between the 2 lateral maxillary processes during their fusion in the origin of the hard palate. The purpose of this report was to relate a case of a median palatine cyst, discussing the rarity of the lesion, its pathogenesis, and the different modalities that could be used for the correct treatment of this pathologic entity.
Keywords: Nonodontogenic cyst; hard palate; pathology; jaw cyst